Evaluating a transdiagnostic acceptance and commitment therapy psychoeducation intervention. (4th October 2017) - Cartwright, Jessica; Hooper, Nic
Abstract: Psychoeducation courses have gained some empirical support as effective early intervention strategies. Many of these courses reflect traditional cognitive behaviour therapy (CBT) thinking but psychoeducation courses based on other approaches are beginning to emerge. One such course, ' ACTivate Your Life ', is based on acceptance and commitment therapy (ACT). The aim of this preliminary investigation is to evaluate a four-session (eight-hour) ACT psychoeducation intervention delivered within the Abertawe Bro Morgannwg University (ABMU) Health Board. Participants were invited to complete four outcome measures (assessing depression, anxiety, self-esteem and life satisfaction) and two process measures (assessing mindfulness self-efficacy and psychological flexibility) at pre- and post-intervention. Statistical analysis indicated that participants' scores across each of the measured domains showed highly significant changes. These results suggest that a brief psychoeducation ACT course may be useful in helping people in need of early psychological intervention, and that further research is now needed to provide a definitive evaluation of its effectiveness.